Toward an Arboreal Poetics - Moe, Aaron M. (Lagoonscapes, 2022)
This is the third of four dialogues between the characters ‘M’ and ‘L’. In the second dialogue, “Planetary Poiesis”, the pair begin to discover how patterns of bifurcation in the cosmos have a deep kinship with patterns of bifurcation in human thought and language. However, the concept of arboreal poetics puts this idea under pressure, opening up further insights into the relationship between bifurcation and poiesis. Moreover, the term arboreal poetics (not unlike zoopoetics) has the potential to point in several directions at once. The aim here is to imagine several possible categories that can help map the vast terrain of the relationship between trees and poiesis.